Impatiens alboarenicola, a new species of Balsaminaceae from north-western Madagascar - Fujimoto, Yutaro; Tagane, Shuichiro; Rabarison, Harison; Andriamahasetra, Rova N.; Komada, Natsuki; Kitajima, Kaoru (Phytotaxa, 2024)
A new species of Impatiens, I. alboarenicola (Balsaminaceae), is described and illustrated from Ankarafantsika National Park, north-western Madagascar. This species is similar to I. barthlottii and I. tsingycola in leaf and flower shape, but clearly distinguished from the former by its shorter stature, absence of a tuber at the stem base, solitary (rarely 2) flowers in the axils of leaves, and smaller flowers, and from the latter by its smaller leaf blades with fewer pairs of teeth on the dentate leaf margin, solitary (rarely 2) flowers in the axils of leaves, and saccate spur-like projection located at ca. 5 mm below the apex of the lower petal lobe of the lateral united petals (vs. at the apex of the lower petal lobe).